Ijp : the book of surfaces - Legendre, George L. 1965- (Architectural Association, 2003)
At a time when architectural discourse and practice are brimming with references to new geometries, [this book] turns its back on the habitual perception of the 3D surface as a photosensitive, colourful and somewhat mystifying expanse. Instead, this experimental text approaches its subject through a joint meditation on abstraction, figuration, performance, symbology and form. Several interdependent modes of writing convey a process of thought elaborated in parallel venues, including theoretical essays on the literal and metaphoric meanings of 'superficial', statements of computer programming syntax, recipes, printouts of data streams, indexical poetry, mathematical asides and descriptions of numerically controlled fabrication processes, all of which offer alternative descriptions of the very same thing: the surface as object of knowledge. A rigorous typographic treatment enhanced by custom-programmed graphics stylizes the most technical side of these various threads, weaving them into a coherent narrative for nonspecialists